RUNWAY Y SU CONTRIBUCIÓN EN EL APRENDIZAJE DE LOS ESTUDIANTES DE LA CARRERA DE PEDAGOGIA DE LAS CIENCIAS EXPERIMENTALES INFORMATICA DE LA UNIVERSIDAD TÉCNICA DE BABAHOYO, PERIODO ACADÉMICO ABRIL- AGOSTO 2024. - ZAMBRANO SANDOYA ANAHIS ALEXANDRA (2024)
Constant technological changes have modified learning processes, providing greater academic flexibility and the emergence of new strategies, methods and tools that have facilitated access to information, creating opportunities for learning through NICTs, giving way to the emergence of artificial intelligence as support tool in the process of students' knowledge acquisition. In this way, the research seeks to analyze how the Runway tool based on AI contributes to the learning of students of the Pedagogy of Experimental Sciences in Computer Science at the Technical University of Babahoyo. Therefore, this curricular integration work describes the benefits of AI with the implementation of Runway in the educational context, as well as detailing the dimensions of learning in its different aspects, taking into consideration a population of 369 students. of which the sample corresponds to 189, through which results are obtained about the use of Runway, addressing questions that allow answers to the research problem for the subsequent conclusions that generate a contribution in the educational field.